Contribution of cross-border renewable energy technology transfer on global carbon mitigation: A case study of solar photovoltaic and biogas projects in China and Ethiopia - Ma, Zhiyuan; Guo, Jianbin; Fu, Yan; Yang, Shoujun; Li, Fang; Abebe, Ashenafi; Wang, Jun; Dong, Renjie (International Journal of Agricultural and Biological Engineering, 2025)
Renewable energy technology transfer in developing countries is vital in addressing the global challenges of climate change and energy crises. However, the environmental impact, especially the carbon emission and mitigation properties during technology transfer, has not been explored. In this study, six renewable energy technology transfer projects (four solar photovoltaic and two biogas projects) from China to Ethiopia have been studied using a life cycle assessment to identify the carbon footprint and comparative emission reduction potential between these projects. Results indicated: 1) Solar photovoltaic and biogas technologies exhibit significant differences in greenhouse gas emissions and reduction potential characteristics. 2) Solar photovoltaic technology demonstrates a more competitive effect in terms of carbon emission reduction and efficiency. 3) Biogas technology exhibits a more favorable transfer effect on global mitigation benefits and costs. This study demonstrates that the renewable energy technology transfer project maintains a better low-carbon characteristic and substantially contributes to low-carbon energy transformation and climate change mitigation. Keywords: renewable energy, carbon footprint, technology transfer, life cycle assessment, global carbon mitigation DOI: 10.25165/j.ijabe.20251804.9682 Citation: Ma Z Y, Guo J B, Fu Y, Yang S J, Li F, Abebe A, et al. Contribution of cross-border renewable energy technology transfer on global carbon mitigation: A case study of solar photovoltaic and biogas projects in China and Ethiopia. Int J Agric & Biol Eng, 2025; 18(4): 293–300.